Smart textile coatings and laminates - Smith, William C. (Textile Institute book series., 2019)
Smart Textile Coatings and Laminates, Second Edition, reviews a variety of topics regarding textile coatings and laminates to provide a stimulus for developing new and improved textile products. It addresses coating and laminating processes and techniques and base fabrics and their interaction in coated fabrics. Other sections discuss the different types of smart and intelligent coatings and laminates, including microencapsulation technology, conductive coatings, breathable coatings, phase change materials and their applications in textiles. Many new chapters have been added in this updated edition, including the medical applications of smart coatings, responsive coatings, and the integration of electronics into textiles. With its highly distinguished editor and array of international contributors, this book is a valuable reference for chemists, textile technologists, fiber scientists, textile engineers, and more.